Microstructural Characterization and Mechanical Properties of Direct Quenched and Partitioned High-Aluminum and High-Silicon Steels - Pekka Kantanen (Metals, 2019)
A new experimental steel containing in weight percent 0.3C-2.0Mn-0.5Si-1.0Al-2.2Cr and 0.3C-1.9Mn-1.0Si-1.0Cr was hot rolled in a laboratory rolling mill and directly quenched within the martensite start and finish temperature range. It was then partitioned without reheating during slow furnace cooling to achieve tensile yield strengths over 1100 MPa with good combinations of strength, ductility and impact toughness. Gleeble thermomechanical simulations led to the selection of the partitioning at the temperatures 175 and 225 °C, which produced the desired microstructures of lath martensite with finely divided retained austenite in fractions of 6.5% and 10% respectively. The microstructures were analyzed using light and scanning electron microscopy in combination with electron backscatter diffraction and X-ray diffraction analysis. The mechanical properties were characterized extensively using hardness, tensile and Charpy V impact testing. In tensile testing a transformation induced plasticity mechanism was shown to operate with the less stable, carbon-poorer retained austenite, which transformed to martensite during straining. The auspicious results in respect to microstructures and mechanical properties indicate that there are possibilities for developing tough ductile structural steels through thermomechanical rolling followed by the direct quenching and partitioning route.